2002
DOI: 10.2114/jpa.21.121
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Capacity of Thai Workers in Different Age and Job Categories.

Abstract: The objective of this study was to assess the cardiorespiratory capacity of Thai male and female bluecollar workers in different age and occupational categories. The maximal oxygen uptake (VO 2 max) of 70 men and 56 women was assessed using a submaximal bicycle-ergometer test supplemented with ventilatory gas analyses. The age of the subjects varied from 16 to 55 years. They worked in construction, manual materials handling and metal jobs. For the male subjects the VO 2 max ranged from 1.43 to 3.50 l/min and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…Middle-aged South Asian individuals have been shown to have lower than their European counterparts [31] . Moreover, the healthy subjects in this study had similar (22±2 ml/kg/min) to Thai subjects of the same age as had been reported in a previous study (25.9±3.4 ml/kg/min) [32] . In this study BrS patients had lower than the controls.…”
Section: Discussionsupporting
confidence: 86%
“…Middle-aged South Asian individuals have been shown to have lower than their European counterparts [31] . Moreover, the healthy subjects in this study had similar (22±2 ml/kg/min) to Thai subjects of the same age as had been reported in a previous study (25.9±3.4 ml/kg/min) [32] . In this study BrS patients had lower than the controls.…”
Section: Discussionsupporting
confidence: 86%
“…Heavy and dynamic physical work is still common in many industrial activities such as mining, building and agriculture [1,2]. In the developed countries, 10-20% of workers are engaged in muscular demanding jobs, while in the developing countries all kinds of intensive work are common [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the developed countries, 10-20% of workers are engaged in muscular demanding jobs, while in the developing countries all kinds of intensive work are common [3]. Unbalanced relationship between physical demands and workers' capacities caused adverse health outcomes [1,4,5]. In physically demanding jobs, the aerobic capacity (V O2 ) of workers determines man's power productivity [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In field settings, as well as in occupational medicine, however, the sub-maximal tests are often used [10][11][12][13][14][15][16], as they do not require the expertise and costs associated with maximal exercise testing. Results of these submaximal tests are then used to predict VO 2peak using regression equations (e.g., Astrand test [7]).…”
Section: Introductionmentioning
confidence: 99%